Airborne infection risk during open-air cardiopulmonary resuscitation. Issue 9 (29th June 2021) - Dbouk, Talib; Aranda-García, Silvia; Barcala-Furelos, Roberto; Rodríguez-Núñez, Antonio; Drikakis, Dimitris
Abstract : Aim: Cardiopulmonary resuscitation (CPR) is an emergency procedure where interpersonal distance cannot be maintained. There are and will always be outbreaks of infection from airborne diseases. Our objective was to assess the potential risk of airborne virus transmission during CPR in open-air conditions. Methods: We performed advanced high-fidelity three-dimensional modelling and simulations to predict airborne transmission during out-of-hospital hands-only CPR. The computational model considers complex fluid dynamics and heat transfer phenomena such as aerosol evaporation, breakup, coalescence, turbulence, and local interactions between the aerosol and the surrounding fluid. Furthermore, we incorporated the effects of the wind speed/direction, the air temperature and relative humidity on the transport of contaminated saliva particles emitted from a victim during a resuscitation process based on an Airborne Infection Risk (AIR) Index. Results: The results reveal low-risk conditions that include wind direction and high relative humidity and temperature. High-risk situations include wind directed to the rescuer, low humidity and temperature. Combinations of other conditions have an intermediate AIR Index and risk for the rescue team. Conclusions: The fluid dynamics, simulation-based AIR Index provides a classification of the risk of contagion by victim's aerosol in the case of hands-only CPR considering environmental factors such as wind speed and direction, relative humidity and temperature. Therefore, we recommend that rescuers perform a quick assessment of their airborne infectious risk before starting CPR in the open air and positioning themselves to avoid wind directed to their faces.